2021
DOI: 10.1017/s1368980021001415
|View full text |Cite
|
Sign up to set email alerts
|

Recall of government healthy eating campaigns by consumers in five countries

Abstract: Objective: To examine awareness and recall of healthy eating public education campaigns in five countries. Design: Data were cross-sectional and collected as part of the 2018 International Food Policy Study. Respondents were asked whether they had seen government healthy eating campaigns in the past year; if yes (awareness), they were asked to describe the campaign. Open-ended descriptions were coded to indicate recall of specific campaigns. Logistic models regressed awareness of healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The public especially referred to C4L campaign as a perceived unadvertised policy, whose name was familiar but they were often unaware of its purpose. A recent cross-sectional study of 5,466 adults in the UK [ 68 ] showed that 18% of participants indicated awareness of public health campaigns and only 3% mentioned C4L as one such campaign, mainly people from higher education backgrounds. Policymakers focused on the role of media and how it can enhance or thwart policy perceptions and highlighted incorrect and inconsistent messages.…”
Section: Discussionmentioning
confidence: 99%
“…The public especially referred to C4L campaign as a perceived unadvertised policy, whose name was familiar but they were often unaware of its purpose. A recent cross-sectional study of 5,466 adults in the UK [ 68 ] showed that 18% of participants indicated awareness of public health campaigns and only 3% mentioned C4L as one such campaign, mainly people from higher education backgrounds. Policymakers focused on the role of media and how it can enhance or thwart policy perceptions and highlighted incorrect and inconsistent messages.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, historically and culturally, women traditionally provide food in the household, potentially explaining the overall higher nutrition knowledge [ 36 ]. Higher scores in the dietary guidelines and knowledge of food choices sections may have resulted from government campaigns [ 26 , 27 , 37 ]. However, lower knowledge in the food choices and the diet–disease relationship sections suggests that carers experienced difficulty in understanding more complex nutrition information compared with basic guidelines and general information [ 26 , 27 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Public health campaigns promoting food consumption and daily diet have been implemented through national programs, utilizing public dietary recommendations [45]. The appropriateness of interventions relies on their alignment with individuals' daily priorities, constraints, and the prevailing cultural values of their social environment [46,47]. Variations in people's interpretation of health can lead to notable variations in behavior; thus, nutrition education could be enhanced by designing customized intervention campaigns that effectively address the health-related motivations of specific subgroups [48][49][50].…”
Section: Literature Reviewmentioning
confidence: 99%